PERBEDAAN STATUS ANEMIA BERDASARKAN KONSUMSI ZAT BESI (Fe) DAN LAMA MENSTRUASI PADA SISWI SMK NEGERI 1 TABANAN - ageng siti zaenab; Ida Ayu Eka Padmiari; Desak Putu Sukraniti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Anemia is one of the health problems throughout the world, especially in developing countries, where an estimated 30% of the world's population suffer from anemia. Normal Hb levels in adolescent girls ≥ 12 g / dl. Anemia occurs in adolescents. Anemia in adolescents is anemia caused by lack of intake of nutrients needed for the formation of hemoglobin, which is iron. The purpose of this study was to determine differences in anemia status based on iron consumption and menstrual duration. This study was an observational study with a cross-sectional approach at SMK Negeri 1 Tabanan in January - March 2020. The study population was grade X students of SMK Negeri 1 Tabanan and the sample was 100 people. Anemia status data samples were collected by measuring hemoglobin levels using a Hb meter. Consumption of iron nutrients obtained through interviews 2x24 hour recall form and menstrual long form. Data were analyzed descriptively and analytically using independent t-test. As many as 97.0% of the sample were not anemic, 89.0% consumed iron with more categories, 100% with normal menstrual periods. The results of statistical analysis, it is known that the consumption of iron variables that affect the anemia status of the sample obtained p value ɑ (p 0.05) which means there are differences in anemia status based on iron consumption. Analysis of differences in anemia status and menstrual length obtained p value ɑ (p 0.05) which means there was no difference in anemia status based on menstrual durationKeywords: iron consumption (Fe), menstrual duration and anemia status